Apolipoprotein E-Mimetic COG1410 Reduces Acute Vasogenic Edema following Traumatic Brain Injury - Cao, Fang (J Neurotrauma, 2016)
The degree of post-traumatic brain edema and dysfunction of the blood–brain barrier (BBB) influences the neurofunctional outcome after a traumatic brain injury (TBI). Previous studies have demonstrated that the administration of apolipoprotein E-mimetic peptide COG1410 reduces the brain water content after subarachnoid hemorrhage, intra-cerebral hemorrhage, and focal brain ischemia. However, the effects of COG1410 on vasogenic edema following TBI are not known. The current study evaluated the effects of 1 mg/kg daily COG1410 versus saline administered intravenously after a controlled cortical impact (CCI) injury on BBB dysfunction and vasogenic edema at an acute stage in mice. The results demonstrated that treatment with COG1410 suppressed the activity of matrix metalloproteinase-9, reduced the disruption of the BBB and Evans Blue dye extravasation, reduced the TBI lesion volume and vasogenic edema, and decreased the functional deficits compared with mice treated with vehicle, at an acute stage after CCI. These findings suggest that COG1410 is a promising preclinical therapeutic agent for the treatment of traumatic brain injury.